Entrepreneurship As a Field of Research: A Response to Zahra and Dess, Singh, and Erikson - Shane, Scott; Venkataraman, S. (Academy of Management Review, 2001)
The authors respond to various comments concerning their article “The Promise of Entrepreneurship as a Field of Research.” They state that they have little interest in building walls between the fields of entrepreneurship and strategic management but instead feel that the field of entrepreneurship needs to create its own conceptual framework that is different from frameworks in other fields such as organizational behavior, operations management, and strategic management. They feel that focusing primarily on small or new businesses leads entrepreneurial research to focus too much attention on questions more pertaining to strategic management than entrepreneurship. They suggest that research can't be focused on profitability of new internet ventures due to the instability of this industry.